The Insertion and Management of External Ventricular Drains: An Evidence-Based Consensus Statement - Fried, Herbert I; Nathan, Barnett R; Rowe, A. Shaun; Zabramski, Joseph M; Andaluz, Norberto; Bhimraj, Adarsh; Guanci, Mary McKenna; Seder, David B; Singh, Jeffrey M (Neurocritical care, 2016)
External ventricular drains (EVDs) are commonly placed to monitor intracranial pressure and manage acute hydrocephalus in patients with a variety of intracranial pathologies. The indications for EVD insertion and their efficacy in the management of these various conditions have been previously addressed in guidelines published by the Brain Trauma Foundation, American Heart Association and combined committees of the American Association of Neurological Surgeons and the Congress of Neurological Surgeons. While it is well recognized that placement of an EVD may be a lifesaving intervention, the benefits can be offset by procedural and catheter-related complications, such as hemorrhage along the catheter tract, catheter malposition, and CSF infection. Despite their widespread use, there are a lack of high-quality data regarding the best methods for placement and management of EVDs to minimize these risks. Existing recommendations are frequently based on observational data from a single center and may be biased to the authors’ view. To address the need for a comprehensive set of evidence-based guidelines for EVD management, the Neurocritical Care Society organized a committee of experts in the fields of neurosurgery, neurology, neuroinfectious disease, critical care, pharmacotherapy, and nursing. The Committee generated clinical questions relevant to EVD placement and management. They developed recommendations based on a thorough literature review using the Grading of Recommendations Assessment, Development, and Evaluation system, with emphasis placed not only on the quality of the evidence, but also on the balance of benefits versus risks, patient values and preferences, and resource considerations.